2008
DOI: 10.1152/ajpgi.90288.2008
|View full text |Cite
|
Sign up to set email alerts
|

Glucose increases synaptic transmission from vagal afferent central nerve terminals via modulation of 5-HT3 receptors

Abstract: Acute hyperglycemia has profound effects on vagally mediated gastrointestinal functions. We have reported recently that the release of glutamate from the central terminals of vagal afferent neurons is correlated directly with the extracellular glucose concentration. The present study was designed to test the hypothesis that 5-HT(3) receptors present on vagal afferent nerve terminals are involved in this glucose-dependent modulation of glutamatergic synaptic transmission. Whole-cell patch-clamp recordings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 81 publications
3
51
0
Order By: Relevance
“…Our chosen concentrations of 0.2, 3, and 5 mM extracellular glucose, therefore, provide a closer mimic of the range of concentrations that may be encountered by NTS neurons in vivo than previous whole cell patch-clamp studies in the region, where large decreases from 10 to 3 or 0 mM, or large increases from elevated baselines of 10 mM to 20 or 30 mM glucose have been used (2,40). These studies, as well as others using extracellular recordings, have found between 20 and 81% of NTS neurons respond to changes in extracellular glucose concentrations, with contradicting reports of the predominance of GE vs. GI phenotypes (2,10,28,40,41,47). Our observation that 56% of NTS neurons are glucose-responsive is similar to those of the most physiological previous studies, where 51-56% of NTS neurons responded to 2 mM changes in glucose concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…Our chosen concentrations of 0.2, 3, and 5 mM extracellular glucose, therefore, provide a closer mimic of the range of concentrations that may be encountered by NTS neurons in vivo than previous whole cell patch-clamp studies in the region, where large decreases from 10 to 3 or 0 mM, or large increases from elevated baselines of 10 mM to 20 or 30 mM glucose have been used (2,40). These studies, as well as others using extracellular recordings, have found between 20 and 81% of NTS neurons respond to changes in extracellular glucose concentrations, with contradicting reports of the predominance of GE vs. GI phenotypes (2,10,28,40,41,47). Our observation that 56% of NTS neurons are glucose-responsive is similar to those of the most physiological previous studies, where 51-56% of NTS neurons responded to 2 mM changes in glucose concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…As with vagal sensory somata, glucose induces the trafficking of 5-HT3 receptors to the membrane of vagal sensory terminals, the tonic activation of which increases glutamate release onto NTS neurons (528). Earlier studies have also shown that glucose is able to modulate the activity of brainstem neurons; hepatic vagal afferent fibers that were inhibited by an increase in glucose levels, for example, innervate NTS neurons that are also inhibited by local application of glucose (3), whereas other NTS neurons are excited by an increase in glucose levels (2, 124, 125, 543, 544).…”
Section: Diabetes and Gastrointestinal Reflexesmentioning
confidence: 99%
“…Further studies demonstrated that, as with vagal sensory somata, glucose induces the trafficking of 5-HT3 receptors to the membrane of vagal sensory nerve terminals, the activation of which increases glutamate release (Wan and Browning, 2008b). 5-HT 3 receptors on vagal afferent terminals appear to be activated tonically; in fact, the 5-HT 3 receptor antagonist, ondansetron, decreases action potential dependent and independent synaptic transmission to second order NTS neurons implying an ongoing activation of these receptors (Wan and Browning, 2008b).…”
Section: Effects Of Glucose On Central Vagal Neurocircuitsmentioning
confidence: 99%